Students’ Perception of Teaching and Learning And Its Use In Quality Assurance - Ulil Albab; M. Agung Ayubi; Agnes Sinaga; Marwa; Citrana Sitohang (International Journal of Pedagogy, 2024)
In this research, we explore students' perceptions of teaching and learning, focusing on its relevance to quality assurance. Employing a quantitative method, we aim to understand the extent to which students on English Education Department, Faculty of Education and Vocational Science value various instruments associated with their perceptions of teaching and learning in the context of quality assurance. Data was Collected from thirty respondents using questionnaire. The study's findings reveal that students consistently recognize the significance of teaching and learning practices in maintaining quality assurance, as explicitly the mean score as Moderate (M=3.91). As a conclusion drawn from these results, it is imperative for educators to strategically enhance students' interest in order to amplify the perceived value of teaching and learning processes, thereby contributing to an enriched educational experience and reinforcing the overall quality assurance framework.